(untitled) (Economic Journal of Nepal, 2015)
Vital Events Registration System (VERS) is an important source to generate and update population data regularly on vital registration. Realizing its importance Nepal government has initiated to start it from the beginning of the 1960s and started since 1977 backing by law. Despite the policies and plans of action of the Nepal government and support from various international agencies, the system could not be an effective instrument to generate regular data on population. The data generated from this source is not complete and reliable for public use till date. The Economic Journal of Nepal Vol. 35, No. 4, October-December 2012 (Issue N0. 140) Page: 235-251